Hypertension Care in Ukraine : Breakpoints and Implications for Action - World Bank (World Bank, Washington, DC, 2019)
Hypertension is one of the leading causes of preventable mortality in Ukraine. It is estimated that high systolic blood pressure was responsible for 42 percent of total deaths in 2016, which is among the highest rates in the world. This report presents key findings from an analysis of the continuum of hypertension care in Ukraine, where the World Bank implements a technical assistance program to support reforms and governance in the health sector. The analysis found significant gaps in detection, treatment monitoring and treatment adherence in hypertension care. The largest breakpoints were blood pressure monitoring at the frequency recommended by the protocol (67 and 71 percent gap in compliance in Lviv and Poltava regions) and achieving normal blood pressure while on treatment (76 and 65 percent gap among patients with monitoring data in Lviv and Poltava regions). The analysis provided lessons with policy implications, including more systematic screening to detect hypertension early and link cases to effective treatment, and a monitoring focus on patients with stage 2 and 3 hypertension and those with co-morbidities like diabetes to prevent poor outcomes. Treatment for blood pressure control is cost-effective in all regions of the world, and in Ukraine improved hypertension care would save lives, reduce disability and save resources in health care.